Land remise income and remise price during China's transitional period from the perspective of fiscal decentralization and economic assessment. (January 2016) - Hong, Zhang; Yi, Zhang; Tiantian, Chen
Highlights: In view of the current outstanding problem of "land finance", the paper constructs a panel data model based on the provincial panel data during 1998–2012, followed by an empirical analysis of whether land remise size and price during China's transitional period are combinedly affected by fiscal decentralization and economic target assessment. The results show that land remises will influence local economic growth through fiscal relations and, in turn, the local governments' fiscal behaviors and economic indicators will affect the land remise scale and price. This paper concludes that, under fiscal decentralization, local governments obtain the balance of payments through the sale of more land, resulting in a rapid increase in land remise scale and price; under the economic target assessment, the local government will use the agreement to sell industrial land at a low price and use the "bid invitation, auction and listing" method to sell commercial land at a high price. In addition, the scale, proportion and prices of the "bid invitation, auction and listing" remise mode are far higher than those of the agreement mode. This phenomenon appears more obviously in regions with a strong degree of financial dependence and a high economic development level. Abstract: In view of the current outstanding problem of "land finance", this paper constructs a panel data model based on the provincial panel data from 1998 to 2012, followed by an empirical analysis of whether land remise income and the remise price during China's transitional period are combinedly affected by fiscal decentralization and economic target assessment. The results show that land remises will influence local economic growth through fiscal relations and, in turn, the local governments' fiscal behaviors and economic indicators will affect the land remise scale and price. This paper concludes that, under fiscal decentralization, local governments obtain the balance of payments through the sale of more land, resulting in a rapid increase in land remise scale and price; under the economic target assessment, the local government will use the agreement to sell industrial land at a low price and use the "bid invitation, auction and listing" method to sell commercial land at a high price. In addition, the scale, proportion and prices of the "bid invitation, auction and listing" remise mode are far higher than those of the agreement mode. This phenomenon appears more obviously in regions with a strong degree of financial dependence and a high economic development level.